2006
DOI: 10.1007/s11051-005-9034-9
|View full text |Cite
|
Sign up to set email alerts
|

The seminal literature of nanotechnology research

Abstract: Report Documentation PageForm Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 168 publications
0
28
0
Order By: Relevance
“…With regard to scientific publications, Kostoff and his co-authors (Kostoff et al 2006a(Kostoff et al , b, 2007a) in a series of papers analyzed the records of Science Citation Index (SCI), Social Science Citation Index (SSCI) and Engineering Compendex publications and found that although the growth of the global nanotechnology scientific articles is a worldwide phenomenon, the most rapid growth in publications during the past decade has occurred in the East Asian nations, notably China and South Korea. While the United States remains the leader in the production of aggregate nanotechnology research articles, China has achieved parity or has even taken the lead in some selected nanotechnology sub-areas.…”
Section: Who Is Winning the Global Nanorace?mentioning
confidence: 99%
“…With regard to scientific publications, Kostoff and his co-authors (Kostoff et al 2006a(Kostoff et al , b, 2007a) in a series of papers analyzed the records of Science Citation Index (SCI), Social Science Citation Index (SSCI) and Engineering Compendex publications and found that although the growth of the global nanotechnology scientific articles is a worldwide phenomenon, the most rapid growth in publications during the past decade has occurred in the East Asian nations, notably China and South Korea. While the United States remains the leader in the production of aggregate nanotechnology research articles, China has achieved parity or has even taken the lead in some selected nanotechnology sub-areas.…”
Section: Who Is Winning the Global Nanorace?mentioning
confidence: 99%
“…In addition, it is well known that in free space, the stable atomic configuration of a nanocluster of a material may differ significantly from the crystalline lattice of the bulk state because of the surface effect [422][423][424][425]. In Section 5.2, it was mentioned that an elastically strained and coherent InAs thin film with the zinc-blende lattice on the GaAs(001) substrate should be mechanically unstable.…”
Section: Critical Size For the Structural Transformation On The Nanosmentioning
confidence: 99%
“…In the fields of nanoscale research, these areas of research connect back to seminal citations in the scientific literature that include, but are not limited to, surfaces, thin films and multilayers, materials, nanowires and catalysts, quantum dots (QDs), carbon nanotubes (CNTs), titanium dioxide, optics and photonics, and electron and atomic force microscopes. Today we also have scientific literature that cover fullerenes, nanotoxicology, nanosensors, molecular genetics, self -assembled mono-layers, nanophotonics, and nanoelectronics, among other fields (Kostoff et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the fields of nanoscale research, these areas of research connect back to seminal citations in the scientific literature that include, but are not limited to, surfaces, thin films and multilayers, materials, nanowires and catalysts, quantum dots (QDs), carbon nanotubes (CNTs), titanium dioxide, optics and photonics, and electron and atomic force microscopes. Today we also have scientific literature that cover fullerenes, nanotoxicology, nanosensors, molecular genetics, self -assembled mono-layers, nanophotonics, and nanoelectronics, among other fields (Kostoff et al, 2006).Because of nanotechnology's interdisciplinary nature, terms are often contested; the rationale for using 'nanotechnology' as a catch-all frame of reference here is because the term has condensed in the public imagination, at least for those who have heard of, or have an understanding of, the term. Outside of specialist fields, however, the term is largely still unknown, as the public awareness research we present here shows.…”
mentioning
confidence: 99%